先化简,在求值(a^2-b^2)/a÷[(2ab-b^2)/a-a),其中a=1+√2,b=1-√2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/06 23:21:23
先化简,在求值(a^2-b^2)/a÷[(2ab-b^2)/a-a),其中a=1+√2,b=1-√2先化简,在求值(a^2-b^2)/a÷[(2ab-b^2)/a-a),其中a=1+√2,b=1-√2
先化简,在求值(a^2-b^2)/a÷[(2ab-b^2)/a-a),其中a=1+√2,b=1-√2
先化简,在求值(a^2-b^2)/a÷[(2ab-b^2)/a-a),其中a=1+√2,b=1-√2
先化简,在求值(a^2-b^2)/a÷[(2ab-b^2)/a-a),其中a=1+√2,b=1-√2
(a^2-b^2)/a÷(2ab-b^2)/a-a)
=(a+b)(a-b)/a÷(2ab-b^2-a^2)/a
=(a+b)(a-b)/a乘a/[-(a-b)^2]
=-(a+b)/(a-b)
a=1+√2,b=1-√2
原式
=-2/2√2
=-√2/2
先化简,在求值 a+b/ab÷a/b-b/a 其中a=1/3,b=1/2
先化简,在求值 a=1 b=-2先化简,在求值 a=1 b=—2
先化简,在求值(a+b)(a-b)+(a+b)^-2a^,其中a=3,b=-1/3
先化简,在求值 (a+b)(a-b)+a(2b-b).其中a=1.5,b=2
先化简,在求值:(a^2b-2ab^2-b^3)÷b-(a+b)(a-b),其中a=-1,b=1/2
(a^2b-2ab^2-b^3)÷b-(a+b)(a-b),其中a=二分之一,b=-1(先化简,在求值)xiexie
先化简,在求值:[(a/a-b)-(a^/a^-2ab+b^)]除以(a/a+b)-(a^/a^-b^)+1 其中a=3分之2 b=-3
先化简 在求值[(a+2b)(a-2b)-(a-4b)²]÷4b 其中a=5 b=2急
先化简,在求值:(a+b)(a-b)+b(b-2),其中a= -1,b=1.
a[a+2b]-[a+1]²+2a先化简,在求值a=2,b=二分之一
先化简,在求值a^2-b^2/a÷(2ab-b^2/a-a),其中a=1+√2,b=1-√2
先化简,在求值(a^2-b^2)/a÷[(2ab-b^2)/a-a),其中a=1+√2,b=1-√2
先化简,在求值2a(a+b)-(a+b²),其中a=根号2011,b=根号2010
(2a+b)²-(3a-b)²+5a﹙a-b)先化简,在求值
先化简,在求值:(a-2b)^2+(a-b)(a+b)-2(a-b)(a-3b),其中a=0.5,b=-1
a-(3b-a)-2b,其中a=2 b=-二分之一 先化简在求值,
先化简 再求值a²-2a+b²/a²-b²+b/a+b
先化简,在求值:a(a-2b)+2(a+b)(a-b)+(a+b)的平方,其中a=-二分之一,b=1